Femtosecond charge and spin dynamics in a Co50Pt50 alloy - Martin Pavelka; Simon Marotzke; Ru-Pan Wang; Mohamed F. Elhanoty; Günter Brenner; Siarhei Dziarzhytski; Somnath Jana; W. Dieter Engel; Clemens v. Korff Schmising; Deeksha Gupta; Igor Vaskivskyi; Tim Amrhein; et al. (Structural Dynamics)
The use of advanced x-ray sources plays a key role in the study of dynamic processes in magnetically ordered materials. The progress in x-ray free-electron lasers enables the direct and simultaneous observation of the femtosecond evolution of electron and spin systems through transient x-ray absorption spectroscopy and x-ray magnetic circular dichroism, respectively. Such experiments allow us to resolve the response seen in the population of the spin-split valence states upon optical excitation. Here, we utilize circularly polarized ultrashort soft x-ray pulses from the new helical afterburner undulator at the free-electron laser FLASH in Hamburg to study the femtosecond dynamics of a laser-excited CoPt alloy at the Co L3-edge absorption. Despite employing a weaker electronic excitation level, we find a comparable demagnetization for the Co 3d-states in CoPt compared to previous measurements on CoPd. This is attributed to the distinctly different spin–orbit coupling between 3d and 4d vs 3d and 5d elements in the corresponding alloys and multilayers.